Effect of sperm DNA fragmentation on ICSI outcome: A prospective study - Lakshamanan, Saravanan; Mahalakshmi, Saravanan; Ramya, Harish; Nidhi, Sharma (Clinical Journal of Obstetrics and Gynecology, 2020)
Aim and objectives: The primary aim was to measure the sperm DNA damage and to study the magnitude of sperm DNA damage. Secondary objective was to study the effect of sperm DNA fragmentation on Day 5 Blastocyst expansion (graded 1-5). Results: There is an increase in sperm DNA fragmentation with an increase in age. Increased sperm DNA fragmentation is also associated with abnormal motility and morphology in semen samples. However, there is no reduction in expansion or grade of blastocyst. Conclusion: Sperm DNA fragmentation testing is a useful investigation in unexplained infertility. However, Sperm DNA fragmentation has no significant association with Day 5 embryo grade in ICSI cycles. Thesis work of Fellowship in Reproductive Medicine student: Dr. Ramya Harish